The Campaign: a case study in identity construction through performance - Matthew D. Riddle (Association for Learning Technology, 2009)
This article undertakes a detailed case study of The Campaign, a teaching and learning innovation in media and communications that uses an online educational role-play. The case study draws on the qualitative analysis of classroom observations, online communications and semi-structured interviews, employing an interpretive approach informed by models drawn from social theory and sociotechnical theory. Educational authors argue that online educational role-plays engage students in authentic learning, and represent an improvement over didactic teaching strategies. According to this literature, online role-play systems afford students the opportunity of acting and doing instead of only reading and listening. Literature in social theory and social studies of technology takes a different view of certain concepts such as performance, identity and reality. Models such as performative self constitution and actor network theory ask us to consider the constructed nature of identity and the roles of all of the actors, including the system itself. This article examines these concepts by addressing a series of research questions relating to identity formation and mediation, and suggests certain limitations of the situationist perspective in explaining the educational value of role-play systems.